Effect of surface sealant on the surface roughness of different composites and evaluation of their microhardness - Alev Özsoy; Meltem Mert Eren; Benin Dıkmen; Aylin Cılıngır; Ozge Gurbuz (Istanbul University, 2020)
Purpose The aim of this study was to evaluate the effect of a surface sealant on the surface roughness of different composites and compare their microhardness values. Materials and Methods Sixty disc-shaped specimens were prepared and assigned to 6 groups (n =10). Groups were prepared as follows; Group 1 (Herculite XRV Ultra), Group 2 (Beautifil Bulk Restorative) and Group 3 (Filtek Bulk Fill Posterior Restorative). Groups 4, 5, and 6 were prepared by applying a surface sealant (BisCover LV) on the specimens in groups 1, 2 and 3. Surface hardness of the discs in group 1, 2, and 3 and surface roughness of the discs in all groups were measured using the Vickers hardness test and a profilometer, respectively. One-way ANOVA was used to test for differences among the groups. Results No significant differences were observed in the microhardness and roughness between the experimental and control groups for each restorative materials. Group 3 showed the highest surface hardness and group 4 showed the lowest surface roughness values. Conclusion Using the BisCover LV resin after the polishing step has no significant effect on the surface roughness. The highest hardness values were obtained for the Filtek Bulk Fill Posterior Restorative after the polishing step. The smoothest surfaces were obtained for all experimental groups using the BisCover LV resin after the polishing step, Herculite XRV Ultra showed lower average roughness values than the other materials.